2022
DOI: 10.3389/fnhum.2022.836980
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Report: The Hippocampus and Surrounding Temporal Cortex of Patients With Schizophrenia Have Impaired Blood-Brain Barrier

Abstract: Though hippocampal volume reduction is a pathological hallmark of schizophrenia, the molecular pathway(s) responsible for this degeneration remains unknown. Recent reports have suggested the potential role of impaired blood-brain barrier (BBB) function in schizophrenia pathogenesis. However, direct evidence demonstrating an impaired BBB function is missing. In this preliminary study, we used immunohistochemistry and serum immunoglobulin G (IgG) antibodies to investigate the state of BBB function in formalin-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…These are novel examples of potential interactions between neuronal-based and endothelial-based cell signaling which affects brain development ( Figure 13 ). In this regard, one can see parallels between inflammatory processes in autism and another genetically related developmental disorder, schizophrenia (SCZ) [ 155 , 156 ] In SCZ, inflammatory markers are associated with cortical expansion and impaired blood brain barrier function which correlates with symptom severity [ 157 , 158 ]. Using human induced pluripotent stem cells, SCZ-derived brain endothelial cells have decreased vasculogenesis and permeability, and decreased ZO-1 expression (tight junction protein) with altered cellular localization in the cytoplasm [ 159 ].…”
Section: Discussionmentioning
confidence: 99%
“…These are novel examples of potential interactions between neuronal-based and endothelial-based cell signaling which affects brain development ( Figure 13 ). In this regard, one can see parallels between inflammatory processes in autism and another genetically related developmental disorder, schizophrenia (SCZ) [ 155 , 156 ] In SCZ, inflammatory markers are associated with cortical expansion and impaired blood brain barrier function which correlates with symptom severity [ 157 , 158 ]. Using human induced pluripotent stem cells, SCZ-derived brain endothelial cells have decreased vasculogenesis and permeability, and decreased ZO-1 expression (tight junction protein) with altered cellular localization in the cytoplasm [ 159 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of its bipolar nature, dysfunction of the BBB can arise from, and be further aggravated by, either the CNS or peripheral compartments. Evidence of neurovascular dysfunction has similarly been observed in bipolar disorder ( Kamintsky et al, 2020 ), schizophrenia ( Kirkpatrick and Miller, 2013 ; Axelsson et al, 1982 ; Campana et al, 2023 ; Goldwaser et al, 2022 ), major depressive disorder ( Torres-Platas et al, 2014 ; Gal et al, 2023 ; Najjar et al, 2013 ), and Parkinson's disease ( Al-Bachari et al, 2020 ; Fowler et al, 2021 ).…”
Section: Introductionmentioning
confidence: 92%
“…These features can explain the heterogenous information about astrocytes in SZ. Studies have reported increased BBB permeability in temporal lobe structures, including the hippocampus, in postmortem samples of SZ [ 254 ]. As S1P modulates BBB permeability [ 181 ], further investigations are needed to explore the potential relationship between S1P and BBB dysfunction in SZ.…”
Section: Evidence Of S1p Role In Psychiatric Diseasesmentioning
confidence: 99%